STATE’S MINING RIGHT ON OIL AND GAS INDUSTRIES OF INDONESIA (Normative Research of Act Number 22 Year 2001 About Oil and Gas ) - Ridwan Bashori (Kumpulan Jurnal Mahasiswa Fakultas Hukum, 2013)
ABSTRACTSince the Independence, Indonesia have primary economy income by Oil & GasMining Industries. In the development of law, Oil & Gas Mining Sector havesome problem based on Act No. 22 Year 2001, for instance the state’s miningright, oil & gas Mining Purpose and oil & gas mining development under the law.In the Oil and Gas Concession countries have a position on the sovereignty ofnatural resources of oil and gas to the maximum benefit of the people, the law in dynamics and exploitation of oil and gas have also performed three times thetesting of oil and gas law and produce interpretations Court Constitution of phrase controlled by the state that notion, controlled by the state should be interpreted to include the meaning of control by the state in a broad conception sourced and derived from the people of Indonesia's sovereignty over all sources of wealth, earth, water and the natural riches contained therein, including the therein collective sense of public ownership by the people for the resources in question. People collectively was at cunstructed by the 1945 Constitution mandates the state to make policy (beleid) and the management actions (bestuursdaad), setting (regelendaad), management (beheersdaad), and control (toezichthoudensdaad) for the purpose of overall prosperity of the people. Administration functions (bestuursdaad) conducted by the state government with the authority to issue and revoke licenses facilities (verguning), license (licentie), and concessions (Consessie). Regulatory functions by the state (regelendaad) is done through the legislative authority of the Parliament and the government, and regulation by the Government. Management functions (beheersdaad) carried out through stock ownership (share-holding) and / or through direct involvement in the management of State-owned Enterprises or State Owned Legal Entity as an institutional instrument, through the state, cq Government, leverage its control over the resources to be used for the maximum prosperity of the people. In an effort to find out about understanding the meaning of control by the state Oil and Gas Act, the approach used is to review and analyze the normative issue judicially determined to see the rule of law by analyzing the Law. 22 of 2001 on Oil and Gas. Then, all data were analyzed by descriptive analysis. Based on the research findings, the answers obtained by the state's right to control the natural resources of oil and natural gas both philosophically and legally, as well as the position of the state in the business of oil and gas in the perspective of the Law of Oil and Gas after the decision of the Supreme Constitution. So in the need for a new law in the form of construction that can carry pengusaahan state control in the oil and natural gas in accordance with the mandate of Article 33 UUD 1945 to the maximum benefit of the people.Keywords : State’s Mining Right on oil & gas, Oil & Gas MiningPurpose, and oil & gas Mining Development under the law.